PERAN GREEN SUKUK DALAM MEMPERKOKOH POSISI INDONESIA DI PASAR KEUANGAN SYARIAH GLOBAL - Anggraini, Yulia (El-Barka: Journal of Islamic Economics and Business, 2018)
Abstract: This research was motivated by the development of sukuk in Indonesia from an international perspective in 2016 which gave positive results. Where Indonesia is the big issuer of sukuk with a total issuance of USD 10, 5 billion from the total issuance of sukuk by the government from all over the world. In the midst of the development of sukuk instruments, there are also instruments such as green bonds that offer investments in environmental development. With the presence of green bonds as investment instruments in the environment, a sharia investment instrument has emerged which has the same concentration as a green bond. The instrument is then called green sukuk. Indonesia is listed as a pioneer in the issuance of green bonds in the Southeast Asia region. The purpose of this study is to identify the potential of sukuk green publishing in Indonesia to strengthen Indonesia's position in the global sharia financial market. This study uses a qualitative approach using historical methods. الملخص: يتم تحفيز هذا البحث من خلال نظرة إيجابية من المنظور الدولي حول تطوير الصكوك في إندونيسيا في عام 2016. حيث تعد إندونيسيا المصدر الكبير للصكوك بإجمالي ,510 دولارات أمريكية من إجمالي إصدارات الصكوك من قبل الحكومة من جميع أنحاء العالم. في خضم تطوير أدوات الصكوك، هناك أدوات مثل green bond  التي تقدم استثمارات في التنمية البيئية.بعد وجود هذه الأدوات كأداة استثمار في البيئة ، تظهر أداة استثمار الشريعة التي لها نفس تركيز له  يسمى الصكوك الخضراء green sukuk. ومن هنا تم إدراج إندونيسيا كرائد في إصدار السندات الخضراء في منطقة جنوب شرق آسيا. الغرض من هذه الدراسة هو تحديد إمكانات النشر الأخضر للصكوك في إندونيسيا لتعزيز مكانة إندونيسيا في السوق المالية الشرعية العالمية. تستخدم هذه الدراسة منهجًا كميًا باستخدام الطريقة التاريخية.. Abstrak: Penelitian ini dilatar belakangi oleh adanya perkembangan sukuk di Indonesia dari kacamata internasional pada tahun 2016 yang memberikan hasil positif. Dimana Indonesia merupakan the big issuer sukuk dengan total penerbitan USD 10, 5 Milyar dari total penerbitan sukuk oleh pemerintah dari seluruh dunia. Ditengah perkembangan instrumen sukuk telah hadir juga instrumen berupa green bond yang menawarkan investasi pada pembangunan lingkungan. Dengan hadirnya green bond sebagai instrumen investasi pada lingkungan telah muncul sebuah instrumen investasi syariah yang konsentrasinya sama dengan green bond. Instrumen tersebut kemudian disebut green sukuk. Indonesia tercatat sebagai pionir dalam penerbitan obligasi hijau di kawasan Asia Tenggara. Tujuan  dari penelitian ini adalah mengidentifikasi potensi penerbitan green sukuk di Indonesia memperkokoh posisi Indonesia di pasar keuangan syariah global. Penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode historis.